Some Boethian Themes in J.R.R. Tolkien’s Lord of the Rings - Wicher, Andrzej (Romanica Silesiana, 2021)
There appear to be quite a few parallels between Tolkien’s The Lord of the Rings and Boethius’s The Consolation of Philosophy (Consolatio Philosophiae), and they seem to concern particularly, though not only, the character drawing in Tolkien’s book. Those parallels are preeminently connected with the fact that both Boethius and Tolkien like to think of the most extreme situations that can befall a human. And both are attached to the idea of not giving in to despair, and of finding a source of hope in seemingly desperate straits. The idea that there is some link between Boethius and Tolkien is naturally not new. T.A. Shippey talks about it in his The Road to Middle Earth, but he concentrates on the Boethian conception of good and evil, which is also of course an important matter, but surely not the only one that links Tolkien and Boethius. On the other hand, it is not my intention to claim that there is something in Tolkien’s book of which it can be said that it would have been absolutely impossible without Boethius. Still, I think it may be supposed that just like Boethian motifs are natural in the medieval literature of the West, so they can be thought of as natural in the work of such dedicated a medievalist as J.R.R. Tolkien.